Partial Equilibrium Trade Simulation (PETS) Model: Documentation - Laborde Debucquet, David; Tokgoz, Simla (International Food Policy Research Institute, 2015)
The objective of this AGRODEP Technical Note is two-fold. First, it aims to describe the mathematical structure of and the economic hypothesis behind the Partial Equilibrium Trade Simulation (PETS) model. Second, it gives a practical approach for use of the General Algebraic Modeling System (GAMS) code in running the model for calibration of the baseline scenario and for simulating the changes in trade policy scenarios. PETS is a multi-region, multi-sector, dynamically recursive, and partial equilibrium (PE) model. The model developed in Fontagne, Laborde, and Mitaritonna (2011) focuses on trade policy analysis using disaggregated geographical and sectoral levels of data. This paper provides a perfect illustration of how this model can be used to study trade agreements, and any user of this model is advised to read it. The model emphasizes the demand side, which is specified as a nested CES structure, where the initial regional income is assumed to be fixed. The demand is expressed at various levels of disaggregation matched by increasing substitutability (elasticity of substitution increases with higher level of disaggregation).